Synthesis and growth mechanism of SiC nanofibres on carbon fabrics. Issue 9 (8th February 2017) - Dai, Jixiang; Sha, Jianjun; Zu, Yufei; Shao, Junqi; Lei, Mingkai; Flauder, Stefan; Langhof, Nico; Krenkel, Walter
Abstract : The SiC nanofibres with a length of few millimetres were synthesized successfully on carbon fabrics using a catalyst-free method. Abstract : The SiC nanofibres with a length of few millimetres were synthesized successfully on carbon fabrics using a catalyst-free method. The Si and SiO2 powder mixtures functioned as a source for the generation of gaseous species. Following the chemical vapour reaction route, abundant SiC nanofibres with near stoichiometric composition and high crystallinity were grown on the surfaces of carbon fibres. The phase, morphology and crystal structure were characterized to reveal the nucleation and growth mechanism. SiC nanofibres presented a pagoda structure, which is a consecutive stacking of hexagonal segments with a high density of stacking faults. Combining the fabrication process with an analysis of the morphology and crystal structure, both the vapour–solid mechanism and the screw dislocation-driven mechanism are responsible for the nucleation and the growth of SiC nanofibres in the current study. The significant advantage of the present process is that it can be conveniently implemented and provides an approach to allow the fabrication of SiC nanostructures on a variety of carbonaceous substrates without the assistance of a catalyst, leading to less expensive, long length and high purity production of nanostructures.